2019
DOI: 10.24263/2304-974x-2019-8-3-4
|View full text |Cite
|
Sign up to set email alerts
|

Effect of high pressure processing on meat and meat products. A review

Abstract: High pressure processing of meat is considered the best non-thermal processing technology to prolong the shelf life and safety of meat, semifinished meat and ready-to-eat meat products preserving sensory and nutritional properties. Material and methods. The object of the paper is properties of meat, minced meat products, gel and protein conformation of myofibrillar proteins treated with high pressure. The research method is the analysis and synthesis of the latest study of the world's leading scientific journa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
11
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 17 publications
(11 citation statements)
references
References 98 publications
(132 reference statements)
0
11
0
Order By: Relevance
“…It may affect the combination of protein molecules form, causes the destruction and restructuring of key, which also affects the functional characteristics of protein. Moreover, protein molecule conformation may bring better functional characteristics due to sudden release of pressure after pressure is withdrawn (Gao, Wang, Mu, Shi, & Yuan, ; Mozhaev, Heremans, Frank, Masson, & Balny, ; Sukmanov, Ma, & Li, ). To the best of our knowledge, the effect of techno‐functional properties and protein conformation on low‐sodium pork meat batters treated by high pressure was less studied.…”
Section: Introductionmentioning
confidence: 99%
“…It may affect the combination of protein molecules form, causes the destruction and restructuring of key, which also affects the functional characteristics of protein. Moreover, protein molecule conformation may bring better functional characteristics due to sudden release of pressure after pressure is withdrawn (Gao, Wang, Mu, Shi, & Yuan, ; Mozhaev, Heremans, Frank, Masson, & Balny, ; Sukmanov, Ma, & Li, ). To the best of our knowledge, the effect of techno‐functional properties and protein conformation on low‐sodium pork meat batters treated by high pressure was less studied.…”
Section: Introductionmentioning
confidence: 99%
“…Denaturation of meat proteins by destroying the amino acid chains and elevating the surface hydrophobicity can lead to discoloration and increased brightness (Sukmanov, Hanjun, & Li, 2019). In the thawed samples, the increase in L value was significant at higher electric field strengths; however, no significant increase was observed from 1.5 kV/cm to 2.5 kV/cm electric field strength, which can be related to protein denaturation; so the protein was not denatured until 2.25 kV/cm electric field strength.…”
Section: Resultsmentioning
confidence: 99%
“…After being subjected to high pressure, the fresh meat witnessed a rapid fall in pH and an intense contraction. The red meat pH decreased by 0.6-0.8 units after 100-150 MPa pressure for 1-5 min at 35 • C. However, the pH of white meat reduced more significantly after 10 min of pressurization [97]. It is observed that the WHC of yak meat is increased and then decreased with an increase in pressure and processing time.…”
Section: High Pressure Processingmentioning
confidence: 92%
“…High-pressure processing requires pressures of at least 100 MPa, with the most common range being 100-1000 MPa, and can work in temperatures ranging from −20 • C to 90 • C. At certain temperatures for appropriate time and pressure levels, non-covalent bonds, such as hydrogen bonds, ionic bonds, and hydrophobic bonds, are destroyed. Enzymes, proteins, starch and other molecular biological substances are deactivated, denatured and gelatinized, respectively, and microbes will be killed for the sake of food safety and preservation [97]. During the HPP process, the pH of meat will decrease, and pressure level, treatment time and temperature, muscle type, and meat temperature are some main factors which effect the high level of pH in meat.…”
Section: High Pressure Processingmentioning
confidence: 99%